Upaya mengurangi repair pada hasil pengelasan di Welding School PT XYZ menggunakan metode Fishbone Diagram dan 5W+1H - Satya , Mas Tangguh Afritza; Ernawati, Dira (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ is an oil field service provider company that has succeeded in achieving high welding quality standards in accordance with international requirements. One of the programs at PT XYZ to improve welding quality is the Welding School. The main goal of welding school is to produce welders who are competent and able to produce quality welds. However, when inspecting the welding results, porosity defects were still found so repairs had to be carried out. The aim of this research is to identify the causes of porosity defect factors using the Fishbone Diagram method. The research results explain that porosity defects in welding results are caused by five factors, namely human factors, machine factors, method factors, material factors and environmental factors. Next, recommendations for improvements using the 5W+1H method are given so that they can be used at the PT XYZ welding school as a reference for reducing repairs on welding results.